(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Mallakhamb is combination of Yoga, Gymnastics and Martial Arts. There is various types of mallakhamb such as pole, rope, hanging, niradhar(without support), on cane, on floating platform, mallakhamb with weapons etc. but at competitive level only pole, rope and hanging mallakhamb are being performed by mallakhamb player.In the sport , knee is common injury site. Knee dysfunction leads to long absence from sports and are one of the main causes of permanent sports disability. Common cause of musculoskeletal pain is hypermobility. In mallakhamb players knee dysfunction is diagnosed with the help of KOOS scale. Conservative management is important to correct knee dysfunctions in mallakhamb players. This study has been undertaken to check the prevalence of knee dysfunction in mallakhamb players. Objective: To find out the prevalence of knee dysfunction in mallakhamb players. Method: An observational study was carried out using a cross sectional study design. The study conducted in and around karad, Maharashtra. The samples were chosen using the simple random sampling method. The participants in this study were both males and females who were played state and national level mallakhamb game more than 6years. Subjects who played only national level mallakhamb game and subjects who were not willing to participate in mallakhamb were excluded from this study. Study was conducted using a sample size of 84 mallakhamb players (n= 4pq/L2 ) for a period of 6 months. The materials was used in this study includes paper, pen, data collection sheet, consent form. Results: On the basis of statistical analysis there was significant knee dysfunction in mallakhamb players. Conclusion; After analyzing the data, it was concluded that there is a prevalence of knee dysfunction in mallakhamb players.